(untitled) (Diversity Research: Journal of Analysis and Trends, 2025)
This article examines the role of national cultural components in phraseological units in both English and Russian languages. It explores how idiomatic expressions that incorporate toponyms or historical events reflect national identities, values, and cultural memory. Using examples such as "to meet one’s Waterloo" and "Сибирская душа," the article highlights how language serves as a repository of cultural history and societal norms. By analyzing these expressions, the article provides a deeper understanding of how cultural identity is embedded in language and how it shapes linguistic expressions across different cultures